Simulation of a manufacturing system for high-mix low-volume manufacturing - Koh, Cai Jun (Nanyang Technological University, 2020)
Manufacturing companies are facing an increasingly competitive in an ever-changing environment. With constant advancements in production technology and the advent of Industry 4.0, manufacturing companies must adapt and improve their facilities and tools to enhance their position in the market and to better compete against their rivals. To maintain their competitive edge, manufacturing companies have looked more closely into adopting proven methods to integrate into their manufacturing systems. Simulation is one of the tools within Industry 4.0. Simulation allows the testing of potential changes and improvements to be made to existing systems within a manufacturing facility virtually before implementing them physically. This allows the testing of various system concepts without interrupting the operation of existing systems. Simulation has been proven to serve as an effective tool in contributing towards the long-term improvement of manufacturing systems and can be a primary decision making standard for investments and guide improvement efforts. This project aims to build a simulation for a low-volume high-mix manufacturing system. The simulation is to be modelled based on the Festo™ impact line manufacturing system that is already set physically in the Delta Corporate Laboratory. The simulation model is based on the principals of discrete event simulation and to be realised in 3D using the simulation software Visual Components. By investigating the performance level of the system and identifying key weaknesses within the system design, efforts can be made to improve the productivity of a low-volume high-mix manufacturing system.